Flat lithium primary battery

By dividing the positive electrode pellet into regions with varying graphite content to manage expansion, the battery maintains electrical contact and enhances discharge capacity.

JP7620896B2Active Publication Date: 2025-01-24PANASONIC INTELLECTUAL PROPERTY MANAGEMENT CO LTD
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
JP2023535156
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Priority Date
2021-07-13
Filing Date
2022-05-16
Publication Date
2025-01-24
Estimated Expiration
2042-05-16

AI Technical Summary

Technical Problem

Existing flat lithium primary batteries face issues with insufficient electrical connection between the positive electrode pellet and the positive electrode can due to uneven expansion during discharge, leading to increased internal resistance and reduced discharge capacity.

Method used

The positive electrode pellet is divided into a first part with a lower graphite content on the side peripheral surface and a second part with a higher graphite content at the center, promoting differential expansion to maintain contact with the positive electrode can, thereby suppressing side peripheral expansion and enhancing electrical connection.

Benefits of technology

This configuration maintains a good electrical connection between the positive electrode pellet and the positive electrode can, reducing internal resistance and improving discharge capacity.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007620896000010
    Figure 0007620896000010
  • Figure 0007620896000011
    Figure 0007620896000011
  • Figure 0007620896000012
    Figure 0007620896000012
Patent Text Reader

Abstract

The disclosed flat lithium primary battery includes: a case; and, a positive electrode, a negative electrode, a separator, and a non-aqueous electrolytic solution disposed in the case. The positive electrode is provided with a positive electrode pellet having the shape of a cylinder and containing a positive electrode active material, an electroconductive agent, and a binding agent. The electroconductive agent contains graphite. The positive electrode pellet is divided into: a first portion that includes at least a part of the side peripheral surface of the cylinder; and, a second portion. The first portion has an annular section that surrounds at least a part of the second portion. The graphite content in the positive electrode pellet is higher in the second portion than in the first portion.
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to flat lithium primary batteries. [Background technology]

[0002] Flat lithium primary batteries are characterized by their high energy density and high voltage, and therefore have been used as power sources for a variety of electronic devices.

[0003] Various flat lithium primary batteries have been proposed. For example, Patent Document 1 proposes a nonaqueous electrolyte battery in which a recess is formed in the center of the surface of the positive electrode mixture on the side in contact with the separator, and the density of the center of the recess is made higher than the density of the peripheral protrusion side. [Prior art documents] [Patent documents]

[0004] [Patent Document 1] Japanese Utility Model Application Publication No. 2-138852 Summary of the Invention

[0005] The positive electrode expands as the battery is discharged. The expansion of the positive electrode may cause the battery case (positive electrode can) to deform. The expansion of the positive electrode may occur either at the center or at the periphery of the positive electrode pellet, but it basically expands uniformly. Meanwhile, the positive electrode can undergoes deformation such that the bottom bulges, with the corner between the cylindrical part and the bottom of the positive electrode can as a fulcrum. As a result, the amount of deformation of the bottom of the positive electrode can is greater at the center, which is far from the corner that serves as the fulcrum, and therefore there may be insufficient contact between the positive electrode can and the positive electrode pellet at the center of the bottom.

[0006] As a result, the central portion of the positive electrode pellet is more likely to lose electrical connection with the positive electrode can than the peripheral portion, causing an increase in internal resistance and making it difficult to obtain sufficient discharge capacity.

[0007] In particular, in the configuration of the lithium primary battery described in Patent Document 1, the positive electrode pellet is prone to expand at the periphery, while the expansion of the concave central portion is suppressed, so that when the positive electrode can is deformed, the electrical connection with the positive electrode can at the central portion is likely to be cut off, and the increase in resistance during discharge may not be sufficiently suppressed. As a result, it is difficult to achieve a high discharge capacity.

[0008] In order to improve the electrical connection between the positive electrode pellet and the positive electrode can, it is possible to provide a current collecting member such as an L-shaped ring or an expanded metal, but this would reduce the volume occupied by the power generating element by the volume occupied by the current collecting member, resulting in a decrease in discharge capacity.

[0009] A flat lithium primary battery according to one aspect of the present disclosure includes a case, and a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte disposed within the case. The positive electrode includes a cylindrical positive electrode pellet including a positive electrode active material, a conductive agent, and a binder. The conductive agent includes graphite. The positive electrode pellet is divided into a first portion including at least a portion of a side surface of the cylinder, and a second portion. The first portion has an annular portion surrounding at least a portion of the second portion, and the graphite content of the positive electrode pellet is greater in the second portion than in the first portion.

[0010] This flat lithium primary battery has a large discharge capacity. [Brief description of the drawings]

[0011] [Figure 1A] FIG. 1 is a schematic cross-sectional view of an example of a configuration of a lithium primary battery according to an embodiment of the present disclosure. [Figure 1B] FIG. 1B is a plan view of the positive electrode of the lithium primary battery shown in FIG. 1A. [Diagram 2] 4A to 4C are diagrams showing examples of the distribution shape and arrangement of first and second portions in a positive electrode pellet. [Diagram 3] 4A to 4C are diagrams showing examples of the distribution shape and arrangement of first and second portions in a positive electrode pellet. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0012] Hereinafter, an embodiment of the present disclosure will be described. In the following description, an embodiment of the present disclosure will be described by way of example, but the present invention is not limited to the example described below. In the following description, specific numerical values ​​and materials may be exemplified, but other numerical values ​​and materials may be applied as long as the effects of the present disclosure can be obtained.

[0013] (Flat lithium primary battery) A flat lithium primary battery according to an embodiment of the present disclosure (hereinafter, may be simply referred to as a "lithium primary battery") includes a case, and a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte solution disposed within the case. The positive electrode and the negative electrode face each other with the separator interposed therebetween. The positive electrode includes a cylindrical positive electrode pellet containing a positive electrode active material, a conductive agent, and a binder. The conductive agent included in the positive electrode contains graphite.

[0014] The positive electrode pellets are housed in a case and are electrically connected to the case. The case is also called a "positive electrode case" or a "positive electrode can." Thus, the case functions as a positive electrode terminal.

[0015] The positive electrode pellet usually has a cylindrical shape (or a disk shape) with a side surface extending in the circumferential direction surrounding the central axis. The cylindrical shape of the positive electrode pellet has a top surface and a bottom surface that are connected to the side surface and located on opposite sides of the central axis. Here, for the cylindrical positive electrode pellet, the surface that is electrically connected to the positive electrode pellet case (positive electrode can) is the bottom surface of the cylinder, and the surface that faces the negative electrode via the separator is the top surface of the cylinder.

[0016] The positive electrode pellet is divided into a first portion including at least a part of the side surface of the cylinder, and a second portion. As described later, the first portion and the second portion have different graphite contents. The first portion includes at least a part of the side surface of the cylinder. The second portion is, for example, a region including the center of the cylinder and surrounded by the first portion. The first portion has an annular portion surrounding at least a part of the second portion. The at least a part of the side surface of the cylinder included in the first portion of the positive electrode pellet surrounds the central axis over the entire circumference in the circumferential direction.

[0017] The graphite content of the positive electrode pellet is higher in the second portion than in the first portion. The higher the percentage of graphite in the material constituting the positive electrode, the easier the positive electrode expands with discharge. Therefore, by increasing the percentage of graphite in the second portion compared to the first portion, i.e., by making the percentage of graphite in the first portion lower than the second portion, the expansion of the periphery of the positive electrode pellet is relatively suppressed, and the positive electrode pellet expands so that the center expands relative to the periphery. As a result, the case expands while the positive electrode pellet maintains a state in which it is in close contact with the positive electrode can in response to the expansion of the positive electrode pellet, and good electrical connection between the positive electrode pellet and the case is maintained. As a result, the increase in internal resistance during discharge is suppressed. In addition, the energy stored in the battery can be effectively utilized to the end, improving the discharge capacity.

[0018] In order to suppress the expansion of the positive electrode pellets in the peripheral portion and promote the expansion of the positive electrode pellets in the central portion, i.e., the region near the central axis of the cylinder, the graphite content in the second portion is preferably 4 parts by mass or more greater than the graphite content in the first portion. In order to suppress the expansion of the positive electrode pellets in the peripheral portion, the graphite content in the first portion may be 4 parts by mass or less. In the above, the graphite content means parts by mass relative to 100 parts by mass of the positive electrode active material.

[0019] Carbon materials such as hard carbon, soft carbon, and graphite are used as conductive agents added to the positive and negative electrodes. Among carbon materials, graphite has a graphene layer in which carbon atoms are bonded to form a hexagonal network and developed in a planar manner. The greater the degree of development of the graphene layer, the larger the volume of the graphite particle, and one graphite particle may contact multiple positive electrode active material particles. For example, when one graphite particle contacts two positive electrode active material particles, the graphite particle contacts the surface of one positive electrode active material particle in a certain graphene layer. The graphite particle may contact the surface of the other positive electrode active material particle in the graphene layer, or may contact the surface of the other positive electrode active material particle in a graphene layer stacked above or below the graphene layer with which one positive electrode active material particle contacts. When one positive electrode active material particle expands due to discharge, the graphene layer of graphite in contact with one positive electrode active material particle acts as a "lever" to cause the other positive electrode active material particle to move. As a result, in the second portion having a large graphite content, the expansion of the positive electrode pellet is effectively promoted while maintaining a certain degree of distance between the positive electrode active material particles.

[0020] Graphite refers to a material with a developed graphite crystal structure. In general, the average interplanar spacing d of the (002) plane measured by X-ray diffraction method is 002 It refers to a carbon material with a diameter of 0.340 nm or less. Examples of graphite include amorphous graphite, scaly graphite, flake graphite, and expanded graphite. Expanded graphite is a material in which an acid component such as sulfuric acid is intercalated between the graphene layers of graphite, and the acid component is volatilized by applying heat to expand the interlayer distance. Graphene composed of a single layer to about 10 graphene layers is included in graphite. It is desirable that graphite accounts for 90% by mass or more of the conductive agent.

[0021] Since the graphene layer is sufficiently developed in the planar direction and the effects of the present disclosure are easily achieved, the graphite preferably includes at least one selected from the group consisting of expanded graphite, flake graphite, and graphene. It is desirable that 90 mass % or more of the graphite is at least one selected from the group consisting of expanded graphite, flake graphite, and graphene.

[0022] The higher the flexibility of graphite, i.e., the lower the rigidity, the more the adhesion between the graphite and the active material particles is improved during pellet molding. On the other hand, the lower the flexibility of graphite, i.e., the higher the rigidity, the more likely the expansion of the active material particles contributes to the expansion of the positive electrode pellet. Among graphites, expanded graphite, flake graphite, and graphene are flat shapes having a layered structure. The long side of the flat shape is related to the particle size. The thickness of the flat shape is shorter than the long side, and the interlayer distance and thickness are related to flexibility and rigidity. Flake graphite is preferred in that it has a small interlayer distance and a large thickness, resulting in high rigidity. Graphene is preferred in that it has a small interlayer distance, but a small thickness, resulting in high flexibility. Expanded graphite is most preferred in that it has a good balance between rigidity and flexibility, resulting from a large interlayer distance and a large thickness. In addition to a single layer, graphene includes a layer of multiple hexagonal mesh layers (for example, about 10 layers).

[0023] In the positive electrode pellet, the first portion having a low graphite content is a region including the side surface (side surface of a cylinder) of the positive electrode pellet, and surrounds at least a part of the second portion having a high graphite content. The first portion may be formed in an annular shape along the side surface of the positive electrode pellet so as to surround the second portion. The thickness (width) of the annular portion in the direction of the central axis (central axis of the cylinder) of the positive electrode pellet may be the same as the width of the side surface of the positive electrode pellet (height of the cylinder), or may be smaller than the width of the side surface of the positive electrode pellet (height of the cylinder). That is, the second portion may be exposed in a part of the side surface on the top side and / or bottom side of the cylindrical positive electrode pellet.

[0024] In the positive electrode pellet, the second portion having a high graphite content may be a region including at least a part of the central axis of the positive electrode pellet (the central axis of the cylinder). The second portion may be a region having the same thickness as the positive electrode pellet in the axial direction of the cylinder so as to include the entire central axis of the positive electrode pellet (the central axis of the cylinder). The thickness of the second portion in the axial direction of the cylinder may be smaller than the thickness of the positive electrode pellet. In other words, in the region including the central axis of the top surface and / or bottom surface of the positive electrode pellet having a cylindrical shape, the first portion may be exposed, or the second portion may be exposed.

[0025] When the positive electrode pellet is viewed from the central axis direction, the larger the cross-sectional area of ​​the annular portion of the first portion in a cross section perpendicular to the central axis is relative to the cross-sectional area of ​​the second portion, the more the expansion of the side periphery of the positive electrode pellet is suppressed, and the central portion of the positive electrode pellet expands relative to the side periphery. As a result, in the bottom portion including the bottom surface of the positive electrode pellet, the amount of expansion of the central portion closer to the central axis is greater than that of the side periphery closer to the side periphery, and the difference in position in the central axis direction between the side periphery and the central portion is greater. In the positive electrode pellet, the minimum value of the distance from the central axis of the positive electrode pellet to the annular portion of the first portion is preferably 90% or less (more preferably 80% or less) of the radius of the positive electrode pellet. In other words, in the positive electrode pellet, the boundary between the annular portion of the first portion and the second portion is preferably located at a position where the distance from the central axis of the positive electrode pellet is 90% or less, more preferably 80% or less, of the radius of the positive electrode pellet. In this case, the bulge of the center of the positive electrode pellet is sufficiently large relative to the periphery, and even if the case (positive electrode can) bulges, it is easy to maintain good electrical connection between the positive electrode pellet and the case.

[0026] Since the second portion of the positive electrode pellet selectively expands more than the first portion of the positive electrode pellet during discharge, good electrical connection between the positive electrode pellet and the case is maintained even when the case (positive electrode can) expands. In this case, by sufficiently increasing the contact area between the portion of the positive electrode pellet that maintains good electrical connection with the case, mainly the second portion and the case, the effect of suppressing the increase in internal resistance during discharge is enhanced, and the discharge capacity can be further increased. From this viewpoint, it is preferable that the maximum value of the distance from the central axis of the positive electrode pellet to the second portion is 50% or more, more preferably 60% or more, of the radius of the positive electrode pellet in the positive electrode pellet. In other words, it is preferable that the boundary between the annular portion of the first portion and the second portion is located at a position where the distance from the central axis of the positive electrode pellet is 50% or more, more preferably 60% or more, of the radius of the positive electrode pellet in the positive electrode pellet.

[0027] Within the positive electrode pellet, the boundary between the annular portion of the first portion and the second portion is preferably located at a position where the distance from the central axis of the positive electrode pellet is 50% or more and 90% or less of the radius of the positive electrode pellet, and more preferably at a position where the distance is 60% or more and 80% or less.

[0028] The thickness (width) of the first portion in the central axis direction is preferably 50% or more of the thickness of the positive electrode pellet at the annular portion. Similarly, the thickness of the second portion in the central axis direction is preferably 50% or more of the thickness of the positive electrode pellet. The positions of the annular portion and the second portion in the central axis direction within the positive electrode pellet are not particularly limited, and they may be disposed on one side toward the positive electrode can side within the positive electrode pellet, or on one side toward the negative electrode or separator side within the positive electrode pellet.

[0029] The positive electrode pellet having the first and second portions can be manufactured, for example, by putting the positive electrode mixture for forming the first portion into a mold to provisionally mold the first portion, then arranging the provisionally molded first portion and the positive electrode mixture for forming the second portion inside a mold for forming a positive electrode pellet, and pressurizing the whole into a pellet shape; alternatively, putting the positive electrode mixture for forming the second portion into a mold to provisionally mold the second portion, then arranging the provisionally molded second portion and the positive electrode mixture for forming the first portion inside a mold for forming a positive electrode pellet, and pressurizing the whole into a pellet shape. A part of the mold for forming the first portion and the mold for forming the positive electrode pellet may be common. Here, the positive electrode mixture for forming the first portion and the positive electrode mixture for forming the second portion each contain a positive electrode active material, a conductive agent, and a binder, but the graphite content of the conductive agent is different. The graphite content of the positive electrode mixture for forming the first portion is smaller than the graphite content of the positive electrode mixture for forming the second portion.

[0030] In the positive electrode pellet, the binder contained in the first portion and the binder contained in the second portion may be different. The second portion preferably contains polytetrafluoroethylene (PTFE) as a binder from the viewpoint of not hindering the expansion promotion effect of graphite. PTFE has a binding structure in which it is entangled in a mesh-like shape with the active material and the conductive agent in a fibrous state, so it is highly flexible and hardly hinders the expansion of the positive electrode pellet caused by graphite. In contrast, the binder contained in the first portion preferably contains tetrafluoroethylene-hexafluoropropylene copolymer (FEP) as a binder from the viewpoint of suppressing the expansion of the positive electrode in the first portion. FEP is melted by heat treatment at high temperature, spreads between the active material and the conductive agent, and resolidifies to have a binding structure in close contact with no gaps, so that it is easy to suppress the expansion of the positive electrode pellet.

[0031] The configuration of the lithium primary battery according to one embodiment of the present disclosure will be described more specifically below.

[0032] The cross-sectional view of Fig. 1A shows an example of the configuration of a lithium primary battery (coin type or button type) of this embodiment. The lithium primary battery 10 of Fig. 1A includes a positive electrode 11, a separator 12, a negative electrode 13, and a case 20. The case 20 includes a positive electrode case 21 that functions as a positive electrode terminal, a sealing plate 22 that functions as a negative electrode terminal, and a gasket 23 disposed between the positive electrode case 21 and the sealing plate 22. The positive electrode 11 and the negative electrode 13 face each other with the separator 12 sandwiched therebetween.

[0033] A positive electrode 11, a separator 12, a negative electrode 13, a gasket 23, and a non-aqueous electrolyte 24 are arranged between a positive electrode case 21 and a sealing plate 22, and the positive electrode case 21 is sealed by bending the upper part of the positive electrode case 21 inward and crimping it.

[0034] FIG. 1B is a plan view of the positive electrode 1. The positive electrode 11 includes a positive electrode pellet 91, which is a molded body that contains a positive electrode active material, a conductive agent, and a binder and is pressure-molded into a pellet shape (cylindrical shape). The positive electrode pellet 91 has a side surface 1C that extends in a circumferential direction Dc surrounding a central axis 11C that extends in a central axis direction Da that is a vertical direction, and a top surface 1A and a bottom surface 1B that are connected to the side surface 1C and located on opposite sides of the central axis 11C. The conductive agent includes graphite. The positive electrode 11 is divided into a first portion 11A and a second portion 11B due to differences in composition. The first portion 11A can be arranged (for example, annularly) along the side surface 1C so as to include at least a part of the cylindrical side surface 1C and surround at least a part of the second portion 11B. The second portion 11B is a portion of the positive electrode 11 other than the first portion 11A. The graphite content in the second portion 11B is greater than the graphite content in the first portion 11A. The first portion 11A has a portion 1D of the side peripheral surface 1C of the positive electrode pellet 91. The portion 1D of the side peripheral surface 1C extends along the side peripheral surface 1C over the entire circumference in the circumferential direction Dc. The portion 1D of the side peripheral surface 1C may be the entire side peripheral surface 1C. The portion 1D of the side peripheral surface 1C may be a part of the side peripheral surface 1C, in which case the second portion 11B has a portion 1E of the side peripheral surface 1C of the positive electrode pellet 91.

[0035] 2 and 3 show examples of the shape and arrangement of the first portion 11A and the second portion 11B in the positive electrode 11. In Fig. 2 and Fig. 3, for configuration examples 1 to 6, the distribution shape of the first portion 11A and the second portion 11B in a cross section of the positive electrode 11 when cut along a plane including the central axis 11C of the positive electrode 11, and the distribution shape of the first portion 11A and the second portion 11B on the top surface 1A and the bottom surface 1B of the positive electrode 11 are respectively shown. The top surface 1A of the positive electrode 11 is a negative electrode facing surface facing the negative electrode 13, and the bottom surface 1B is a positive electrode case facing surface facing the positive electrode case 21.

[0036] In the configuration examples 1 to 6, the first portion 11A has an annular portion 11P formed so as to extend over the entire circumference in the circumferential direction Dc along the side peripheral surface 1C of the positive electrode 11, which is cylindrical. The annular portion 11P surrounds the side peripheral surface 2C of the second portion 11B. The annular portion 11P is exposed over the entire circumference in the circumferential direction Dc of the side peripheral surface 1C of the positive electrode 11. However, the side peripheral surface 1C may have an area in which the first portion 11A is not exposed and the second portion 11B is exposed in a part of the circumferential direction Dc. The second portion 11B may also be generally cylindrical in shape in accordance with the shape of the positive electrode 11. In this case, the upper surface 2A and the bottom surface 2B of the second portion 11B are defined in the same manner as the upper surface 1A and the bottom surface 1B of the positive electrode 11 (positive electrode pellet 91). That is, the upper surface 2A of the second portion 11B faces the negative electrode 13, and the bottom surface 2B faces the positive electrode case 21.

[0037] In the configuration example 1 shown in FIG. 2, the first portion 11A is exposed over the entire side circumferential surface 1C of the positive electrode 11, and is an annular portion 11P that is a predetermined value or more away from the central axis 11C of the cylindrical positive electrode 11. In this case, the second portion 11B is a region that is a predetermined value or less away from the central axis 11C of the cylindrical positive electrode 11. The thickness (width) of the first portion 11A and the second portion 11B in the central axis direction Da is equal to the thickness (height of the cylinder) of the positive electrode 11 in the central axis direction Da. In this case, the top surface 1A and the bottom surface 1B of the positive electrode 11 each have a region where the first portion 11A and the second portion 11B are exposed. The first portion 11A is exposed on the side of the side circumferential surface 1C of the top surface 1A and the bottom surface 1B of the positive electrode 11, and the second portion 11B is exposed on the central axis 11C side.

[0038] The distance from the central axis 11C of the positive electrode 11 that defines the boundary between the first portion 11A and the second portion 11B is preferably in the range of 50% to 90% of the radius of the positive electrode 11, and more preferably in the range of 60% to 80%.

[0039] 2, the thickness (width) of the first portion 11A in the central axis direction Da may be smaller than the thickness (height of the cylinder) of the positive electrode 11 in the central axis direction Da. In this case, the first portion 11A is not exposed to at least one of the top surface 1A and the bottom surface 1B of the positive electrode 11, and only the second portion 11B is exposed. Configuration example 2 is an example in which the second portion 11B is exposed over the entire surface of the bottom surface 1B of the positive electrode 11, and configuration example 3 is an example in which the second portion 11B is exposed over the entire surface of the top surface 1A of the positive electrode 11.

[0040] As shown in configuration examples 4 and 5 of FIG. 3, the first portion 11A may cover at least one of the upper surface 2A and the bottom surface 2B of the second portion 11B in addition to covering the side peripheral surface 2C of the second portion 11B. In this case, the second portion 11B is not exposed to at least one of the upper surface 1A and the bottom surface 1B of the positive electrode 11, and only the first portion 11A is exposed. Configuration example 4 is an example in which the first portion 11A covers the bottom surface 2B of the second portion 11B, and the first portion 11A is exposed over the entire surface of the bottom surface 1B of the positive electrode 11. Configuration example 5 is an example in which the first portion 11A covers the upper surface 2A of the second portion 11B, and the first portion 11A is exposed over the entire surface of the upper surface 1A of the positive electrode 11. In the case of configuration examples 4 and 5 of Figure 3, the portion of the first portion 11A that is perpendicular to the central axis 11C and faces the second portion 11B in the radial direction Dr away from the central axis 11C is the annular portion 11P, and the thickness (width) of the annular portion 11P in the central axis direction Da is equal to the thickness of the second portion 11B in the central axis direction Da.

[0041] Configuration example 6 shown in Figure 3 is an example in which, like configuration examples 2 and 3, the thickness (width) of the first portion 11A in the central axis direction Da is smaller than the thickness (height of the cylinder) of the positive electrode 11 in the central axis direction Da, and is an example in which the first portion 11A is not exposed on both the top surface 1A and the bottom surface 1B of the positive electrode 11, and only the second portion 11B is exposed.

[0042] The thickness (width) of the first portion 11A constituting the annular portion 11P in the central axis direction Da is preferably 50% or more of the thickness (cylinder height) of the positive electrode 11 in the central axis direction Da.

[0043] The positive electrode 11 (positive electrode pellet 91) shown in configuration examples 1 to 3 and 6 can be manufactured, for example, by putting a positive electrode mixture for the first portion 11A into a mold to provisionally mold the first portion 11A, then disposing the provisionally molded positive electrode mixture for the first portion 11A and the second portion 11B inside a mold for forming the positive electrode pellet 91, and pressure-molding the whole into a pellet shape. On the other hand, the positive electrode 11 (positive electrode pellet 91) shown in configuration examples 4 and 5 can be manufactured, for example, by putting a positive electrode mixture for the second portion 11B into a mold to provisionally mold the second portion 11B, then disposing the provisionally molded positive electrode mixture for the second portion 11B and the first portion 11A inside a mold for forming the positive electrode pellet, and pressure-molding the whole into a pellet shape.

[0044] There are no particular limitations on the components of the positive electrode other than those described above, and the components other than the positive electrode (negative electrode, separator, nonaqueous electrolyte, case, etc.), and the battery may include components other than those described above (for example, a current collector). The components other than the positive electrode may be known components used in general lithium primary batteries.

[0045] Examples of other components of the lithium primary battery are described below.

[0046] (positive electrode) The positive electrode includes a positive electrode active material. The positive electrode may further include other materials (such as known materials used in the positive electrodes of general lithium primary batteries). The positive electrode includes a binder and a conductive agent. The conductive agent includes graphite. Materials other than graphite may be included as conductive agents. Examples of other materials include carbon-based materials such as carbon black (e.g., ketjen black). Examples of binders include fluorocarbon resins such as polytetrafluoroethylene (PTFE), perfluoroalkoxyalkane (PFA), tetrafluoroethylene-hexafluoropropylene copolymer (FEP), and ethylene-tetrafluoroethylene copolymer (ETFE), polyvinylidene fluoride (PVDF).

[0047] The mass of the binder contained in the positive electrode may be in the range of 1.2 to 6% (for example, in the range of 1.5 to 3%) of the mass of the positive electrode active material contained in the positive electrode. By including a binder in this range, the formation of the positive electrode becomes easier, and in particular mass productivity is improved.

[0048] The positive electrode active material contained in the positive electrode includes manganese dioxide. A positive electrode containing manganese dioxide exhibits a relatively high voltage and has excellent pulse discharge characteristics. The manganese dioxide may be in a mixed crystal state containing a plurality of crystal states. The positive electrode may contain manganese oxides other than manganese dioxide. Examples of manganese oxides other than manganese dioxide include MnO, Mn 3 O 4 , Mn 2 O 3 , Mn 2 O 7 The main component of the manganese oxide contained in the positive electrode is preferably manganese dioxide.

[0049] A part of the manganese dioxide contained in the positive electrode may be doped with lithium. If the amount of lithium doped is small, a high capacity can be ensured. Manganese dioxide and manganese dioxide doped with a small amount of lithium are Li x MnO 2 (0≦x≦0.05). The average composition of the manganese oxide in the positive electrode is Li x MnO 2 (0≦x≦0.05) is preferable. The Li ratio x generally increases as the discharge of the lithium primary battery progresses. The Li ratio x is preferably 0.05 or less in the initial discharge state of the lithium primary battery.

[0050] The positive electrode may contain other positive electrode active materials used in lithium primary batteries. Examples of other positive electrode active materials include graphite fluoride. The percentage of Li in the total positive electrode active material is x MnO 2 The proportion of is preferably 90 mass % or more.

[0051] As the manganese dioxide, electrolytic manganese dioxide is preferably used. If necessary, electrolytic manganese dioxide that has been subjected to at least one of neutralization, washing, and calcination may be used. Electrolytic manganese dioxide is generally obtained by electrolysis of an aqueous manganese sulfate solution.

[0052] By adjusting the conditions during electrolytic synthesis, the crystallinity of manganese dioxide can be increased and the specific surface area of ​​electrolytic manganese dioxide can be reduced. x MnO 2 The BET specific surface area of 2 / g or more 50m 2 / g or less, 2 / g or more 30m 2 / g or less. x MnO 2 The BET specific surface area of ​​the LixMnO2 separated from the positive electrode taken out of the battery can be measured by a known method, for example, using a specific surface area measuring device (for example, manufactured by Mountec Co., Ltd.) based on the BET method. 2 can be used as a measurement sample.

[0053] Positive electrode active material Li x MnO 2 The average particle size is preferably, for example, 20 to 50 μm. Here, the average particle size means the median diameter D50 on a volume basis, and is measured by a laser diffraction type particle size distribution measuring device.

[0054] (Negative electrode) The negative electrode contains at least one selected from the group consisting of metallic lithium and a lithium alloy as a negative electrode active material. The negative electrode may contain metallic lithium or a lithium alloy, or may contain both metallic lithium and a lithium alloy. For example, a composite containing metallic lithium and a lithium alloy may be used for the negative electrode.

[0055] The lithium alloy is not particularly limited, and an alloy used as a negative electrode active material of a lithium primary battery can be used. Examples of the lithium alloy include Li-Al alloy, Li-Sn alloy, Li-Ni-Si alloy, and Li-Pb alloy. The content of metal elements other than lithium contained in the lithium alloy is preferably 0.05 to 15 mass % from the viewpoint of ensuring discharge capacity and stabilizing internal resistance.

[0056] (Separator) A lithium primary battery usually includes a separator interposed between a positive electrode and a negative electrode. As the separator, it is preferable to use a porous sheet formed of an insulating material that is resistant to the internal environment of a lithium primary battery. Specifically, a nonwoven fabric made of a synthetic resin, a microporous membrane made of a synthetic resin, or a laminate of these may be used.

[0057] Examples of synthetic resins used for nonwoven fabrics include polypropylene, polyphenylene sulfide, polybutylene terephthalate, etc. Examples of synthetic resins used for microporous membranes include polyolefin resins such as polyethylene, polypropylene, and ethylene-propylene copolymers, etc. The microporous membrane may contain inorganic particles as necessary.

[0058] (electrolyte) There is no particular limitation on the electrolytic solution 24, and any non-aqueous electrolytic solution generally used in lithium primary batteries may be used. For example, the electrolytic solution 24 may be a non-aqueous electrolytic solution in which lithium salt or lithium ions are dissolved in a non-aqueous solvent.

[0059] The non-aqueous solvent may be an organic solvent that can be generally used in non-aqueous electrolytes for lithium primary batteries. The non-aqueous solvent may be an ether, an ester, a carbonate ester, or the like. The non-aqueous solvent may be dimethyl ether, γ-butyl lactone, propylene carbonate, ethylene carbonate, 1,2-dimethoxyethane, or the like. The non-aqueous electrolyte may contain one type of non-aqueous solvent, or may contain two or more types of non-aqueous solvents.

[0060] From the viewpoint of improving the discharge characteristics of the lithium primary battery, the non-aqueous solvent preferably contains a cyclic carbonate having a high boiling point and a chain ether having a low viscosity even at low temperatures. The cyclic carbonate preferably contains at least one selected from the group consisting of propylene carbonate (PC) and ethylene carbonate (EC), and PC is particularly preferred. The chain ether preferably has a viscosity of 1 mPa·s or less at 25°C, and particularly preferably contains dimethoxyethane (DME). The viscosity of the non-aqueous solvent is measured at 25°C at a shear rate of 10,000 (1 / s) using a microsample viscometer m-VROC manufactured by Rheosens.

[0061] As the lithium salt, for example, a salt generally used as a solute in a lithium primary battery can be used. Such a lithium salt includes, for example, LiCF 3 SO 3 , LiN(CF 3 SO 2 ) 2 , LiClO 4 , LiBF 4 , LiPF 6 , LiR a SO 3 (R a is a fluoroalkyl group having 1 to 4 carbon atoms), LiFSO 3 , LiN(SO 2 R b )(SO 2 R c )(R b and R c are each independently a fluoroalkyl group having 1 to 4 carbon atoms), LiN(FSO 2 ) 2 , LiPO 2 F 2、 LiB(C 2 O 4 ) 2 , LiBF 2 (C 2 O 4 The non-aqueous electrolyte solution 24 may contain one type of these lithium salts or may contain two or more types of them.

[0062] The concentration of lithium ions contained in the electrolytic solution 24 (total concentration of lithium salts) is, for example, 0.2 to 2.0 mol / L, and may be 0.3 to 1.5 mol / L.

[0063] The electrolyte 24 may contain additives as necessary. Examples of such additives include propane sultone, vinylene carbonate, etc. The total concentration of such additives contained in the non-aqueous electrolyte 24 is, for example, 0.003 to 5 mol / L.

[0064] (case) The case 20 (positive electrode case 21 or positive electrode can) can be made of, for example, stainless steel having electrical conductivity.

[0065] The shape of the case 20 of the lithium primary battery (i.e., the shape of the battery) is generally flat. The case 20 may be, for example, a flat rectangular shape or a coin shape (including a button shape). When the lithium primary battery of this embodiment is a coin-shaped lithium primary battery using a coin-shaped case 20, typically, the positive electrode and the negative electrode are each disk-shaped.

[0066] The case 20 may include a positive electrode case 21 functioning as a positive electrode terminal, a sealing plate 22 functioning as a negative electrode terminal, and a gasket 23 disposed between the positive electrode case 21 and the sealing plate 22. There is no particular limitation on the material of the gasket 23, and a material that is generally used for the gasket 23 may be used. Examples of the material of the gasket 23 include resins such as polypropylene (PP), polyphenylene sulfide (PPS), perfluoroalkoxyalkane (PFA), and polyetheretherketone (PEEK).

[0067] <Example> The lithium primary battery of this embodiment will be described in more detail with reference to the following examples, although the present invention is not limited to the following examples.

[0068] Lithium primary batteries A1-A15, B1-B6 (1) Preparation of the positive electrode A positive electrode mixture was prepared by mixing electrolytic manganese dioxide, a conductive agent, and a binder in a predetermined mass ratio. Carbon black and graphite were used as the conductive agent. The graphite was selected from expanded graphite with an average particle size of 50 μm, a thickness of about 3 μm, and an interlayer distance of about 500 nm, flake graphite with an average particle size of about 50 μm, a thickness of about 0.2 μm, and an interlayer distance of about 0.34 nm, and graphene with an average particle size of about 50 μm, a thickness of about 0.01 μm, and an interlayer distance of about 0.34 nm. PTFE or FEP was selected and used as the binder.

[0069] A plurality of types (12 types) of positive electrode mixtures with different conductive agent compositions and / or binder compositions were prepared and used as the positive electrode mixture for forming the first portion 11A or the positive electrode mixture for forming the second portion 11B of the positive electrode. In each positive electrode mixture, the carbon black content was constant at 1 part by mass per 100 parts by mass of manganese dioxide. Table 1 shows the types of graphite and binders contained in each positive electrode mixture and their content ratios. In Table 1, the content ratios are shown in parts by mass per 100 parts by mass of manganese dioxide.

[0070] Among the positive electrode mixtures X1 to X12 shown in Table 1, one of the positive electrode mixtures X1 to X6 was selected as the positive electrode mixture for forming the first portion 11A. The positive electrode mixture for forming the first portion 11A was placed in a predetermined mold and compressed to form a provisional molded body in a ring shape. The provisional molded body had an outer diameter (diameter) of 14.5 mm, an inner diameter (diameter) of 13 mm, and a thickness (width) in the central axis direction of 1.9 mm.

[0071] Furthermore, one of the positive electrode mixtures X1 to X6 shown in Table 1 was selected as the positive electrode mixture for forming the second portion 11B. The provisionally molded body was fitted into a mold for forming a positive electrode pellet, and the inside of the provisionally molded body (the part that becomes the inside of the ring) was filled with the positive electrode mixture for forming the second portion 11B. After that, a cylindrical positive electrode pellet 91 with an outer diameter of 14.5 mm and a height of 1.9 mm was obtained by press molding. In the positive electrode pellet 91, the first portion 11A and the second portion 11B are distributed as shown in Configuration Example 1 of FIG.

[0072] [Table 1]

[0073] (2) Preparation of the negative electrode A disk-shaped negative electrode having a diameter of 16 mm and a thickness of 0.8 mm was obtained by punching out a plate of metallic lithium.

[0074] (3) Preparation of non-aqueous electrolyte Propylene carbonate (PC) and 1,2-dimethoxyethane (DME) were mixed in a volume ratio of 1:1 to obtain a non-aqueous solvent. Lithium perchlorate (LiClO 4 ) was dissolved in the aqueous solution to a concentration of 0.5 mol / L to prepare a non-aqueous electrolyte solution 24.

[0075] (4) Assembly of lithium primary batteries A polypropylene nonwoven fabric (thickness: 0.5 mm) was prepared as a separator. A polypropylene gasket 23 was prepared. A positive electrode case 21 formed by pressing conductive stainless steel with a plate thickness of 0.2 mm was prepared. A sealing plate 22 formed by pressing conductive stainless steel with a plate thickness of 0.25 mm was prepared. Using these positive electrode pellets 91, negative electrode, electrolyte 24, separator, positive electrode case 21, gasket 23, and sealing plate 22, a flat lithium primary battery (CR2032 type) having the structure shown in FIG. 1A was assembled.

[0076] In this manner, test lithium primary batteries A1 to A15 and B1 to B6 having different configurations of the first portion 11A and the second portion 11B were produced, and the following evaluations were carried out.

[0077] (5) Evaluation [Discharge capacity] A discharge output test was conducted in accordance with JIS C 8515:2017, and the discharge capacity was measured.

[0078] The manufactured lithium primary battery was placed in an environment of 20°C. The lithium primary battery was discharged while connected to a load resistance of 15 kΩ until the terminal voltage reached 2.0 V. The amount of discharge charge that flowed until the terminal voltage reached 2.0 V was determined. The amount of discharge charge was measured for 10 lithium primary batteries, and the average value was taken as the discharge capacity (mAh).

[0079] [Measurement of the expansion degree of the positive electrode] The battery after the discharge capacity measurement was disassembled, and the positive electrode pellet 91 was taken out. The positive electrode pellet 91 was placed with the top surface 1A (negative electrode facing surface) facing down so that the central axis 11C coincided with the up-down direction, and the height h1 at the center position of the bottom surface 1B of the positive electrode pellet 91 and the height h2 at the side peripheral portion were measured. The height h2 at the side peripheral portion was calculated by averaging the heights at four positions equiangularly spaced by 90 degrees in the circumferential direction Dc on a circumference located midway between the outer circumference and the inner circumference of the annular portion 11P of the first portion 11A, from the central axis 11C. The height difference Δh (mm) between the center position and the peripheral position of the bottom surface 1B was calculated by Δh=h1-h2.

[0080] The height difference Δh was measured for 10 lithium primary batteries, and the average value was evaluated as the degree of expansion Δ(mm).

[0081] The evaluation results are shown in Table 2. As shown in Table 1, the positive electrode mixtures X1 to X6 have the same type and content ratio of the binder contained in each positive electrode mixture, and differ only in the content of graphite (expanded graphite) contained as a conductive agent. Table 2 also shows the positive electrode mixtures used in each lithium primary battery and the graphite content of the positive electrode mixtures.

[0082] [Table 2]

[0083] In the lithium primary batteries B1 to B6, the composition of the positive electrode mixture is the same in the first portion 11A and the second portion 11B, and the graphite content is also the same in the first portion 11A and the second portion 11B. In this case, there is no difference in the expansion rate between the first portion 11A and the second portion 11B, and the expansion degree Δ is substantially equal to 0. In addition, the discharge capacity is small. In the lithium primary batteries B1 to B6, the discharge capacity tends to decrease as the graphite content is increased and the positive electrode pellet 91 becomes more likely to expand. This is thought to be because the positive electrode pellet 91 expands uniformly throughout, causing the positive electrode case 21 to swell, making it easier for the electrical connection between the positive electrode pellet 91 and the positive electrode case 21 to be broken at the center of the positive electrode pellet 91.

[0084] In contrast, in the lithium primary batteries A1 to A15, the graphite content of the second portion 11B was made higher than that of the first portion 11A (the graphite content of the first portion 11A was made lower than that of the second portion 11B), thereby improving the discharge capacity. In the lithium primary batteries A1 to A15, the center portion of the positive electrode pellet 91 is configured to expand more than the peripheral portion, so the degree of expansion Δ is a positive value. As a result, even when the positive electrode case 21 expands due to the expansion of the positive electrode, it is possible to maintain electrical connection between the positive electrode pellet 91 and the positive electrode case 21 at the center portion of the positive electrode pellet 91, and it is believed that the discharge capacity can be maintained high.

[0085] In particular, in the lithium primary batteries A2 to A5, A7 to A9, A11, A12, and A14 in which the difference in graphite content between the second portion 11B and the first portion 11A was 4 parts by mass or more per 100 parts by mass of the positive electrode active material, the discharge capacity was significantly improved.

[0086] The higher the graphite content of first portion 11A and second portion 11B, the easier it is for positive electrode pellet 91 to expand and the easier it is for electrolyte 24 to be absorbed into positive electrode pellet 91. As a result, less electrolyte 24 is retained in the separator, which may lead to an increase in internal resistance and a decrease in discharge capacity. However, as shown in Table 2, when the graphite content of first portion 11A is in the range of 4 parts by mass or less per 100 parts by mass of the positive electrode active material, the discharge capacity can be maintained high.

[0087] Lithium primary batteries A16 to A18, B7 In the lithium primary batteries B1, A1, and A5, the positive electrode mixture used to form the first portion 11A was changed from X1 to X7. That is, the binder contained in the first portion 11A was changed from PTFE to FEP. Except for this, lithium primary batteries B7, A16, and A17 were fabricated in the same manner as the lithium primary batteries B1, A1, and A5, respectively, and evaluated in the same manner.

[0088] In addition, in the lithium primary battery A15, the positive electrode mixture used to form the first portion 11A was changed from X5 to X8. That is, the binder contained in the first portion 11A was changed from PTFE to FEP. A lithium primary battery A18 was produced in the same manner as the lithium primary battery A15 and evaluated in the same manner.

[0089] The evaluation results are shown in Table 3. Compared with the lithium primary batteries B1, A1, A5, and A15 shown in Table 2, an improvement in discharge capacity can be seen by using FEP as the binder contained in the first portion 11A.

[0090] [Table 3]

[0091] Lithium Primary Batteries A19-A27 In producing the positive electrode, when obtaining a ring-shaped temporary molded body using the positive electrode mixture for forming the first portion 11A, the inner diameter (diameter) of the temporary molded body was changed from 13 mm to 11 mm, 9 mm, and 7 mm, respectively, and multiple types of positive electrode pellets 91 with different volume ratios of the first portion 11A and the second portion 11B were prepared.

[0092] A positive electrode mixture X1 was used to form the first portion 11A, and a positive electrode mixture X2 was used to form the second portion 11B. In the same manner as the lithium primary battery A1, a lithium primary battery A19 having an inner diameter (diameter) of the first portion 11A of 11 mm, a lithium primary battery A20 having an inner diameter (diameter) of the first portion 11A of 9 mm, and a lithium primary battery A21 having an inner diameter (diameter) of the first portion 11A of 7 mm were fabricated and evaluated in the same manner.

[0093] A positive electrode mixture X1 was used to form the first portion 11A, and a positive electrode mixture X6 was used to form the second portion 11B. In the same manner as the lithium primary battery A5, a lithium primary battery A22 having an inner diameter (diameter) of the first portion 11A of 11 mm, a lithium primary battery A23 having an inner diameter (diameter) of the first portion 11A of 9 mm, and a lithium primary battery A24 having an inner diameter (diameter) of the first portion 11A of 7 mm were fabricated and evaluated in the same manner.

[0094] Positive electrode mixture X5 was used to form the first portion 11A, and positive electrode mixture X6 was used to form the second portion 11B. In the same manner as the lithium primary battery A15, a lithium primary battery A25 having an inner diameter (diameter) of the first portion 11A of 11 mm, a lithium primary battery A26 having an inner diameter (diameter) of the first portion 11A of 9 mm, and a lithium primary battery A27 having an inner diameter (diameter) of the first portion 11A of 7 mm were produced and evaluated in the same manner.

[0095] The evaluation results are shown in Table 4. In Table 4, the inner diameter (R 1 The outer diameter of the first portion 11A (the outer diameter of the positive electrode pellet 91) (diameter) is R 2 As R 1 / R 2 The results for the lithium primary batteries A1, A5, and A15 are also shown in Table 2. From Table 4, R 1 R 2 In the range of 50% to 90% of the radius of the positive electrode pellet 91 (in other words, when the boundary between the first portion 11A and the second portion 11B is located at a position where the distance from the central axis 11C of the positive electrode pellet 91 is 50% to 90% of the radius of the positive electrode pellet 91), a high discharge capacity can be easily achieved. 1 R 2 In the range of 60% or more and 80% or less of the above, a significantly high discharge capacity can be realized.

[0096] [Table 4]

[0097] Lithium Primary Batteries A29-31 In the lithium primary battery A1, the positive electrode mixture used to form the second portion 11B was changed from X2 to X9 or X11. That is, the type of graphite contained in the second portion 11B was changed from expanded graphite to graphene or flake graphite. Except for this, a lithium primary battery A28 including graphene in the second portion 11B and a lithium primary battery A29 including flake graphite in the second portion 11B were fabricated in the same manner as the lithium primary battery A1, and were similarly evaluated.

[0098] In addition, in the lithium primary battery A5, the positive electrode mixture used to form the second portion 11B was changed from X6 to X10 or X12. That is, the type of graphite contained in the second portion 11B was changed from expanded graphite to graphene or flake graphite. Except for this, a lithium primary battery A30 including graphene in the second portion 11B and a lithium primary battery A31 including flake graphite in the second portion 11B were fabricated in the same manner as the lithium primary battery A5, and were similarly evaluated.

[0099] The evaluation results are shown in Table 5. In Table 5, the results of the lithium primary batteries A1 and A5 are also shown by reprinting them from Table 2.

[0100] [Table 5]

[0101] Lithium primary batteries A32-A37 The positive electrode mixture X1 was used to form the first portion 11 A, and the positive electrode mixture X2 was used to form the second portion 11 B. In producing the positive electrode, when a ring-shaped provisional compact was obtained using the positive electrode mixture for forming the first portion 11 A, the thickness (width) in the central axis direction of the provisional compact was changed from 1.9 mm to 0.95 mm or 0.80 mm.

[0102] The provisionally molded body was fitted into a mold for forming a positive electrode pellet 91, and the remaining portion not filled with the provisionally molded body was filled with a positive electrode mixture for forming the second portion 11B. After that, by press molding, a cylindrical positive electrode pellet 91 with an outer diameter (diameter) of 14.5 mm and a height of 1.9 mm was obtained.

[0103] Except for this, lithium primary batteries A32 to A37 were fabricated and evaluated in the same manner as lithium primary battery A1. In lithium primary batteries A32 to A37, the distribution shape of first portion 11A and second portion 11B in positive electrode pellet 91 was set to be either configuration example 2 or 3 in FIG. 2, or configuration example 6 in FIG.

[0104] The evaluation results are shown in Table 6. Table 6 also shows the value of the thickness d in the central axis direction Da of the first portion 11A constituting the annular portion 11P, and the value of the ratio d / D of the thickness d to the thickness D in the central axis direction Da of the positive electrode pellet 91. The results of the lithium primary battery A1 are also shown by reprinting them from Table 2. Table 6 shows that the thickness d in the central axis direction Da of the first portion 11A constituting the annular portion 11P is sufficient if it is 40% or more of the thickness D of the positive electrode pellet 91, and preferably if it is 50% or more of the thickness D of the positive electrode pellet 91.

[0105] [Table 6]

[0106] Lithium Primary Batteries A38~A41 The positive electrode mixture X1 was used to form the first portion 11A, and the positive electrode mixture X2 was used to form the second portion 11B. The positive electrode mixture X2 was placed in a predetermined mold and compressed to form a provisional molding, thereby obtaining a pellet-shaped provisional molding that is the second portion 11B. The provisional molding had an outer diameter (diameter) of 13 mm and a thickness (width) in the central axis direction Da of 0.95 mm or 0.80 mm.

[0107] The provisionally molded body was placed in the center of a mold for forming a positive electrode pellet 91, and the remaining portion not filled with the provisionally molded body was filled with a positive electrode mixture X1 for forming the first portion 11A. After that, a cylindrical positive electrode pellet 91 with an outer diameter (diameter) of 14.5 mm and a height of 1.9 mm was obtained by press molding.

[0108] In this manner, lithium primary batteries A38 to A41 similar to the lithium primary battery A1 were produced, except that the distribution shape of the first portion 11A and the second portion 11B in the positive electrode pellet 91 was as shown in configuration example 4 or 5 in Figure 3, and were similarly evaluated.

[0109] The evaluation results are shown in Table 7. Table 7 also shows the value of the thickness d in the central axis direction Da of the second portion 11B, and the value of the ratio d / D of the thickness d to the thickness D in the central axis direction Da of the positive electrode pellet 91. The results of the lithium primary battery A1 are also shown by reprinting them from Table 2. It can be seen from Table 7 that the thickness d in the central axis direction Da of the second portion 11B is sufficient if it is 40% or more of the thickness D of the positive electrode pellet 91, and is preferably 50% or more of the thickness D of the positive electrode pellet 91.

[0110] [Table 7]

[0111] Lithium Primary Batteries A42-A47 The first portion 11A was formed using a positive electrode mixture X1, and the second portion 11B was formed using a positive electrode mixture X6. Except for this, the lithium primary batteries A42 to A47 were produced in the same manner as the lithium primary batteries A32 to A37 while changing the thickness d in the central axis direction Da of the first portion 11A constituting the annular portion 11P, and were similarly evaluated. That is, the lithium primary batteries A42 to A47 correspond to the lithium primary batteries A32 to A37 in which the graphite content in the second portion 11B was changed from 2 parts by mass to 10 parts by mass per 100 parts by mass of the positive electrode active material.

[0112] The evaluation results are shown in Table 8. Table 8 also shows the value of the ratio d / D of the thickness d in the central axis direction of the first portion 11A constituting the annular portion 11P to the thickness D in the central axis direction Da of the positive electrode pellet 91. The results of the lithium primary battery A5 are also shown by reprinting them from Table 2. Table 8 shows that the thickness d in the central axis direction Da of the first portion 11A constituting the annular portion 11P is sufficient if it is 40% or more of the thickness D of the positive electrode pellet 91, and preferably if it is 50% or more of the thickness D of the positive electrode pellet 91.

[0113] [Table 8]

[0114] Lithium Primary Batteries A48~A51 The first portion 11A was formed using a positive electrode mixture X1, and the second portion 11B was formed using a positive electrode mixture X6. Except for this, the lithium primary batteries A48 to A51 were produced in the same manner as the lithium primary batteries A38 to A41 while changing the thickness d of the second portion 11B in the central axis direction Da, and were similarly evaluated. That is, the lithium primary batteries A48 to A51 correspond to the lithium primary batteries A38 to A41 in which the graphite content in the second portion 11B was changed from 2 parts by mass to 10 parts by mass per 100 parts by mass of the positive electrode active material.

[0115] The evaluation results are shown in Table 9. Table 9 also shows the values ​​of the thickness d of the second portion 11B in the central axis direction Da and the ratio d / D of the thickness d to the thickness D of the positive electrode pellet 91 in the central axis direction Da. The results of the lithium primary battery A5 are also shown by reprinting them from Table 2. Table 9 shows that a high discharge capacity is obtained when the thickness d of the second portion 11B in the central axis direction Da is 40% or more of the thickness D of the positive electrode pellet 91, and an even higher discharge capacity is obtained when the thickness d of the second portion 11B in the central axis direction Da is 50% or more of the thickness D of the positive electrode pellet 91.

[0116] [Table 9]

[0117] In the above embodiment, terms indicating directions such as "upper and lower directions," "top," and "bottom" indicate relative directions determined only by the relative positional relationships of components of a flat lithium primary battery such as a positive electrode and a negative electrode, and do not indicate absolute directions such as the vertical direction. [Industrial Applicability]

[0118] The present disclosure can be used for flat lithium primary batteries. [Explanation of symbols]

[0119] 10 Flat lithium primary battery 11 Positive electrode 11A Part 1 11B 2nd part 11C Center axis 1C Side surface 12 Separator 13 Negative electrode 20 cases 21 Positive electrode case 22 Sealing plate 23 Gasket 91 Positive electrode pellet

Claims

1. A flat lithium primary battery including a case, and a positive electrode, a negative electrode, a separator, and a non-aqueous electrolyte disposed in the case, The positive electrode includes a positive electrode active material, a conductive agent, and a binder, and is provided with a cylindrical positive electrode pellet having a side surface extending in a circumferential direction surrounding a central axis extending in a central axis direction, The conductive agent includes graphite, The positive electrode pellet is divided into a first portion including at least a part of the side peripheral surface of the cylindrical positive electrode pellet, and a second portion, the first portion has an annular portion surrounding at least a portion of the second portion, a graphite content in the positive electrode pellet is greater in the second portion than in the first portion.

2. 2 . The flat lithium primary battery according to claim 1 , wherein the at least a portion of the side peripheral surface of the cylindrical positive electrode pellet included in the first portion of the positive electrode pellet surrounds the central axis over the entire circumference in the circumferential direction.

3. 2. The flat lithium primary battery according to claim 1, wherein a content of the graphite in the second portion relative to 100 parts by mass of the positive electrode active material is 4 parts by mass or more greater than a content of the graphite in the first portion relative to 100 parts by mass of the positive electrode active material.

4. The flat lithium primary battery according to claim 1 , wherein the content of the graphite in the first portion is 4 parts by mass or less with respect to 100 parts by mass of the positive electrode active material.

5. 2. The flat lithium primary battery according to claim 1, wherein within the positive electrode pellet, a boundary between the annular portion and the second portion is located at a position such that a distance from the central axis of the positive electrode pellet is 60% or more of a radius of the positive electrode pellet.

6. 2. The flat lithium primary battery according to claim 1, wherein within the positive electrode pellet, a boundary between the annular portion and the second portion is located at a position such that a distance from the central axis of the positive electrode pellet is 80% or less of a radius of the positive electrode pellet.

7. 2 . The flat lithium primary battery according to claim 1 , wherein a thickness of the positive electrode pellet in the second portion in the direction of the central axis at the position of the central axis is 50% or more of a thickness of the positive electrode pellet.

8. 2. The flat lithium primary battery according to claim 1, wherein the thickness of the annular portion in the central axis direction of the positive electrode pellet is 50% or more of the thickness of the positive electrode pellet.

9. the first portion contains a tetrafluoroethylene-hexafluoropropylene copolymer as the binder, The flat lithium primary battery according to any one of claims 1 to 8, wherein the second portion contains polytetrafluoroethylene as the binder.

10. The flat lithium primary battery according to any one of claims 1 to 8, wherein the graphite includes at least one selected from the group consisting of expanded graphite, flake graphite, and graphene.

11. 11. The flat lithium primary battery of claim 10, wherein the graphite comprises expanded graphite.

12. The flat lithium primary battery according to any one of claims 1 to 8, wherein the positive electrode active material contains manganese dioxide.

Citation Information

Patent Citations

  • JP1990138852U

  • Coin-type lithium battery

    JP1995201323A

  • Flat battery

    JP2008288060A

  • Flat type alkaline primary battery

    JP2019160672A